The case for international emission trade in the absence of cooperative climate policy - Jared C. Carbone; Carsten Helm; Thomas F. Rutherford (Technische Universität Darmstadt, Department of Law and Economics, 2008)
We evaluate the efficacy of international trade in carbon emission permits when countries are guided strictly by their national self-interest. To do so, we construct a calibrated general equilibrium model that jointly describes the world economy and the strategic incentives that guide the design of national abatement policies. Countries' decisions about their participation in a trading system and about their initial permit endowment are made noncooperatively; so a priori it is not clear that permit trade will induce participation in international abatement agreements or that participation will result in significant environmental gains. Despite this, we find that emission trade agreements can be effective; that smaller groupings pairing developing and developed-world partners often perform better than agreements with larger rosters; and that general equilibrium responses play an important role in shaping these outcomes.
Keywords: D7; F18; F42; Q58; 330; Global warming; coalitions; general equilibrium; tradable permits; Klimaveränderung; Emissionshandel; Internationale Zusammenarbeit; Allgemeines Gleichgewicht